O papel da incerteza no planejamento de sistemas de educação a distância - ELIASQUEVICI, Marianne Kogut (2015)
The task of planning a system of distance education (SDE) is a complex process due to the number of components involved, the different views and approaches as to their efficacy, the contending values, the interests at play, and the urgent decisions often needed. This work starts from the experience available in books and articles by the authors, and draws from part of the doctorate thesis of one of them, with the purpose of describing the importance of uncertainty analysis in programs of distance education, thereby contributing to reduce the probability of occurrence of undesirable and/or unexpected events in various situations characterized by complex environments. It describes the trajectory of uncertainty in the perspective of science, and presents a theoretical framework to give support to the problem of planning SDEs. It also mentions the ways in which uncertainties can enter decision processes and the setting up of SDEs, taking as its source a study carried out in the State of Pará. Strategies were devised with a view to improve the articulation of initiatives in the various areas involved, in order to maximize the participation of the different actors and to reinforce the role of distance education as a public policy for social inclusion. In its final considerations, the article emphasizes the applicability of this investigation to other situations. The work aims at contributing to define strategic guidelines for the implementation of SDEs.